Soles dermatoglyphics in the prognosis of sport endowments: forming of soles dermatoglyphics in the Ukrainian population (information 1) - Serhiyenko L.P; Lyshevska V.M (Kharkov National Pedagogical University, 2013)
Comparative indexes are considered for determination of dermatoglyphic markers feet in relation to a sporting gift. In an experiment took part 209 youths and 198 girls in age 17-19 years. Studied conformities to the law of the phenotypical forming of dermatoglyphics of feet at the persons of Ukrainian population. Differential differences are found between the dermatoglyphics of feet for men and women. Distributing of dermatoglyphic phenotype is resulted on two feet for men and women which do not go in for sports. It is established that most often for men and for women phenotype of LW is formed. For men it can find out this phenotype more frequent (39,5%), than for women (26,8%). Phenotype of ALW for people does not meet of both sexes. Last phenotype is distributed mainly evenly: from 3,1 to 12,2% for men and from 5,3 to 14,9% for women. The population presence of dermatoglyphic phenotype of LA has some differences. For women phenotype meets more frequent (19,4%), than for men (13,9%).